INTENSI BERBAGI PENGETAHUAN PADA DOSEN DI UNIVERSITAS “X” - Devi Jatmika (Universitas Bunda Mulia, 2016)
Nowadays, economy has changed from industry era to knowledge based economy. Indonesia as one of developing countries need to build, invest, and focus in the knowledge and technology for the economy growth, because it can benefit to become more equal participant in the global development process. Knowledge is the main part that plays an important role for an organization. Knowledge management is a method to increase the process of sharing, distribution and creating knowledge in an organization. Knowledge sharing is part of the process, where one shares their knowledge and ideas throughdiscussion in order to create new knowledge or new ideas. Lecturers are the asset of university’s development and knowledge sharing intention is a positive attitude that should be developed. The aim of this research is to describe the knowledge sharing intention among lecturers in “X” university. This research used quantitative research. Knowledge sharing intention questionnaire was created based on the Theory of Planned Behavior by Azjen (2006). There was 58 lecturers filled the questionnaire. The result revealed that the knowledge intention sharing among lectures was very low (24.1%), low (34.5%), high(17.2%) and very high (24.1%). The response of some open-ended questions identified some factors that hinder their intention to share knowledge, such as lack of confidence, lack of experiences, the limitation of knowledge, and opportunity to share. Keywords: Knowledge, Knowledge sharing intention, lecturers